214k views
0 votes
Solve for x.
-(5 – 8x)+4x = -89

User Dayra
by
5.1k points

2 Answers

5 votes

Answer:

X= -7

Explanation:

-(5 – 8x)+4x = -89

Or -5 + 8x + 4x = -89

Or -5 + 12x = -89

Or 12x = -89 + 5

Or X = -84/12

Or X = -7

User Snowbear
by
5.7k points
3 votes

Answer:

x = -7

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Equality Properties

Explanation:

Step 1: Define Equation

-(5 - 8x) + 4x = -89

Step 2: Solve for x

  1. Distribute negative: -5 + 8x + 4x = -89
  2. Combine like terms: -5 + 12x = -89
  3. Isolate x term: 12x = -84
  4. Isolate x: x = -7

Step 3: Check

Plug in x into the original equation to verify it's a solution.

  1. Substitute in x: -(5 - 8(-7)) + 4(-7) = -89
  2. Multiply: -(5 + 56) - 28 = -89
  3. Add: -61 - 28 = -89
  4. Subtract: -89 = -89

Here we see that -89 does indeed equal -89.

∴ x = -7 is the solution to the equation.

User Chisholm
by
5.1k points